“The merchants of Tarshish, with all the young lions thereof.” the British Empire, scripture prophecy, and the war of Armageddon, 1914-1918 - Reisenauer, Eric Michael; MacDonald, Nathan 1975-; Mein, Andrew (2017)
The First World War spurred interest among the British people in the eschatological and apocalyptic portions of the Bible. The general scope of the war, as well as its particular course, provided much material to those who interpreted war-time events as heralds of the coming end of the age. Of particular interest was the subject of the British Empire’s place in the unfolding upheaval. The belief in Britain’s identity as God’s instrument of righteousness, whether as the King of the North, the Tarshish power, or the Israel of prophecy, assured many in Britain that their nation would play a paramount role in winning the war and establishing God’s rule on Earth.
Keywords: Apocalypse; First World War; Prophecy; Britain; Israel; Tarshish